Sustainable development through eco-innovation. Empirical evidence from the EU-27 member states - Sipos, Gabriela Lucia; Ionescu, Alin (Journal of Business Economics and Management, 2024)
Increasing concerns for ensuring a sustainable future generated an imperative need to shift toward a circular economy and sustainable innovations. In this framework, eco-innovation becomes essential for achieving sustainable development. The main purpose of this paper is to focus on a more in-depth, original revealing of the influence of eco-innovation on countries’ sustainable development. Thus, five eco-innovation dimensions, components of the Eco-Innovation Index, are considered for a complete approach. This paper first explores the interaction of the five dimensions within the Eco-Innovation Index. Further, the paper analyses the cumulative effects of the five Eco-Innovation Index dimensions on the 17 Sustainable Development Goals components defined by the United Nations. Considering a panel data set of 189 values for the EU27 Member States for seven years and applying the Structural Equation Model (SEM), this paper emphasizes that only three out of five dimensions perform significantly in the Eco-Innovation Index. Moreover, it proved that the Eco-Innovation Index dimensions contribute to achieving 11 of the 17 sustainable development goals (SDGs). Also, the results highlight that significant relationships were revealed only between certain Eco-Innovation Index dimensions and some SDG components. This paper’s conclusions contribute to a deeper understanding of gaining sustainable development through eco-innovation.